THE ENVIRONMENTAL FOOTPRINT OF TRANSPORT CONSUMPTION – AN EDUCATIONAL CHALLENGE FOR GENERATION Z - Jan Chocholáč; Monika Skalska; Dalibor Gottwald; Hana Pavlisova; Vojtech Julak (Perner’s Contacts, 2024)
This paper brings together two very topical and important themes. The first is the issue of the environmental footprint of transport consumption and the second is the current educational challenges of Generation Z representatives. The paper focuses on a combination of both topics, respectively addressing the education of Generation Z on the topic of the environmental footprint of transport consumption. The paper is prepared using a primary representative survey method based on an online questionnaire survey of representatives of Generation Z (secondary school students in the Czech Republic). The aim of the paper is to identify the educational challenges of the generation Z (studying at secondary schools in the Czech Republic) in the thematic area of the environmental footprint of transport consumption. The results clearly show the necessity of using audio-visual educational content and linking theory and practice, for example in the form of case studies. Generation Z wants quick, concise, up-to-date, interesting, and interactive information. Generation Z representatives clearly confirm the need to address human environmental impacts in education, adding that not enough time is devoted to them. They also confirm that there is a lack of study materials in this subject area and that they are not developed in a user-friendly way. Representatives of Generation Z are interested in further education on the environmental footprint of transport consumption. The findings of this paper can help both secondary school teachers, as well as school and curriculum developers and educational policy and strategy makers.